Pengaruh Kesulitan Belajar Karena Gangguan Perkembangan Siswa Kelas XI-1 SMA Negeri 1 Sidoarjo - Mufidah, Cindy Imroatul; Bariza, Marwa Fuha Alilatul; Putri, Ratna Rucita; Aisyah, Shiva Nur; Solekhah, Adistya Aliyus (TSAQOFAH, 2025)
Difficulties Learning difficulties are a disturbance in a child's learning process that can interfere with plans and goals that should be achieved. Learning difficulties are caused by there is a disturbance in the nerve center of the brain which causes speech disorders, reading, writing, counting, and in the comprehension process. This can cause students' academic ability to decline. The purpose of this observation is to determine the learning difficulties due to the development of students in Class XI-1 SMAN 1 Sidoarjo, knowing the development that can interfere with the learning process of students. This observation also aims to find out whether students have learning difficulties in learning when the development of technology has ruled the world, and can analyze how influential the effect of development beats the spirit of learning of students. Preparation of This article uses quantitative and qualitative approaches. The method The research method is based on secondary data derived from observation. The method This research method uses a survey approach, while the data collection is is done through questionnaires, interviews, and direct observation.